Sistemas integrados de gestión HSEQ, más que un requisito exigible (2014)
All companies are exposed to various risks that may come from the external environment or the internal environment, so it is necessary to control negative situations that may weaken the strengths of the company, thus the production quality would improve the competitiveness and unnecessary costs caused by poor control within them would be saved. This article presents the objectives sought by the application of standards that make HSEQ management systems, when a company wants to be certified.